2012
DOI: 10.1111/j.1600-0854.2012.01400.x
|View full text |Cite
|
Sign up to set email alerts
|

The PtdIns3P‐Binding Protein Phafin 2 Mediates Epidermal Growth Factor Receptor Degradation by Promoting Endosome Fusion

Abstract: Phosphatidylinositol 3-phosphate (PtdIns3P) orchestrates endosomal cargo transport, fusion and motility by recruiting FYVE or PX domain-containing effector proteins to endosomal membranes. In an attempt to discover novel PtdIns3P effectors involved in the termination of growth factor receptor signalling, we performed an siRNA screen for epidermal growth factor (EGF) degradation, targeting FYVE and PX domain proteins in the human proteome. This screen identified several potential regulators of EGF degradation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 65 publications
1
33
0
Order By: Relevance
“…More recently, genomewide (Collinet et al, 2010) and targeted (Pedersen et al, 2012) RNAi screens have independently identified SNX15 as a regulator of degradative EGFR sorting, although the details of its role have yet to be described [the latter screen specifically targeted the human proteome for proteins that contain phosphoinositide-binding PX and FYVE domains (Pedersen et al, 2012)]. Human SNX15 is a 342 amino acid protein composed of a central region that includes a proline-rich stretch of three PPPxxP repeats (residues P142 to P181) and an acidic cluster (E 255 EEEDGE 261 ), flanked by an N-terminal SNX-PX domain (F9 to G126) and a C-terminal microtubule-interacting and trafficking (MIT) domain (A267 to P342; Fig.…”
Section: Sorting Nexin Loss-of-function Screen Reveals a Role For Snxmentioning
confidence: 99%
“…More recently, genomewide (Collinet et al, 2010) and targeted (Pedersen et al, 2012) RNAi screens have independently identified SNX15 as a regulator of degradative EGFR sorting, although the details of its role have yet to be described [the latter screen specifically targeted the human proteome for proteins that contain phosphoinositide-binding PX and FYVE domains (Pedersen et al, 2012)]. Human SNX15 is a 342 amino acid protein composed of a central region that includes a proline-rich stretch of three PPPxxP repeats (residues P142 to P181) and an acidic cluster (E 255 EEEDGE 261 ), flanked by an N-terminal SNX-PX domain (F9 to G126) and a C-terminal microtubule-interacting and trafficking (MIT) domain (A267 to P342; Fig.…”
Section: Sorting Nexin Loss-of-function Screen Reveals a Role For Snxmentioning
confidence: 99%
“…mRNA expression analysis was done as described in Pedersen et al, 2012 48 . The primers used in the experiment were QT00035455 for WDFY2 and QT00000721 for TBP for housekeeping (Qiagen).…”
Section: Microscopymentioning
confidence: 99%
“…The subsequent signaling cascades are involved in endocytic transport and endocytic signaling, cytokinesis as well as autophagy (Simonsen and Tooze, 2009;Funderburk et al, 2010;Nezis et al, 2010;Platta and Stenmark, 2011;Pedersen et al, 2012;Schink et al, 2016). In humans, these PIK3C3-dependent processes have a central function in the prevention of tumorigenesis, by ensuring the termination of growth factor receptor signaling, as well as by the engulfment of damaged organelles in autophagosomes, or through prevention of bi-nucleation and genome instability by promoting a correct cytokinesis (Stenmark, 2010;Morris et al, 2015).…”
Section: Introduction: the Principles Of Phosphatidylinositol 3-kinasmentioning
confidence: 99%